METHODS OF COMBINING PHYSICS IN COMPUTER SCIENCE IN SECONDARY EDUCATION SYSTEM BASED ON CLASTER PRINCIPLES - Bediyev Shokir Khudoynazarovich (Galaxy International Interdisciplinary Research Journal, 2022)
The article describes the modern process of effective use of information and communication technologies (ICT) in the educational process in educational institutions, in particular, when teaching physics.